The Decivilizing Process and Urban Working-Class Youth in Scotland - Law, Alex (Social justice, 2011)
The article discusses the impact of decreased socioeconomic divisions and social labeling on self-perceptions among working-class youth in Scotland, particularly focusing on the efforts to eliminate Great Britain's history of a class society. It addresses the denial of the effects of social and economic structure on individual social status, as well as comments on the relationship between efforts to decivilize Great Britain and perceptions of social superiority. Other topics explored include public policy in Great Britain, the changing perception of the label working-class, and social dependency.